Enhanced detection of clinically significant prostate cancer in targeted and non-targeted regions using BiopSee® MRI/ultrasound fusion biopsy - Nakahara, Ken (American journal of clinical and experimental urology, 2025)
This study evaluated the cancer detection profile of magnetic resonance imaging/transrectal ultrasound fusion-guided biopsies (fusion biopsy) using the BiopSee system in patients assessed with the Prostate Imaging Reporting and Data System (PI-RADS) version 2.1, focusing on clinically significant prostate cancer (csPCa) detection in regions of interest (ROI) and non-ROI areas. We retrospectively analyzed 59 patients who underwent fusion biopsy between February and November 2024. Detection rates of csPCa (grade group ≥ 2) were compared between the ROI and non-ROI regions, and clinical and biopsy characteristics were compared between patients with and without csPCa. Univariate logistic regression analysis was performed to identify predictors of csPCa. The median patient age was 74 years, with a median prostate-specific antigen (PSA) level of 8.93 ng/mL. The csPCa detection rate was significantly higher in the ROI than in the non-ROI regions (61% vs. 44%, P = 0.012). Across the cohort, PI-RADS 4 and 5 lesions were more common than PI-RADS 3 lesions. A higher PI-RADS score (4 or 5) was identified as a significant predictor of csPCa detection (odds ratio 5.14, P = 0.034), whereas age, PSA, number of ROIs, and biopsy core numbers were not significant predictors. Fusion biopsy using the BiopSee system achieved a high csPCa detection rate in targeted ROIs, especially for PI-RADS 4 and 5 lesions, while also highlighting the importance of combining systematic biopsy with targeted approaches because of the substantial proportion of csPCa detected in non-ROI regions.